A review of porous automotive sound absorbers, their environmental impact and the factors that influence sound absorption. (2017) - Dunne, Regan Kyle; Desai, Dawood A.; Sadiku, Rotimi
The transport sector accounts for ~25% of worldwide carbon dioxide emissions, where cars and trucks account for the bulk of this. The need for lighter and more efficient vehicles is becoming ever more crucial in light of the current trend in the depletion of petroleum reserves and the increasing effects of global warming. The effect that noise has on vehicle occupants is a growing concern as studies reveal the harmful effects that noise has on the human body. Hence, the automotive industry is under immense pressure to produce automobiles that are more environmentally-friendly. By acquiring available knowledge on the properties of porous sound absorbing materials and understanding the factors that influence sound absorption, designers can reduce vehicle weight and increase passive sound absorption and hence, reduce carbon dioxide emissions and improve vehicle cabin noise levels.